THE EFFECT OF CAPITAL STRUCTURE, INTELLECTUAL CAPITAL AND FIRM SIZE OF FINANCIAL PERFORMANCE BANKING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PE-RIOD 2020 - 2024 - Putri Imanda Rezeki Nasution; Fahmi Natigor Nasution; Sambas Ade Kesuma (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the effect of capital structure, intellectual capital, and company size on the financial performance of banking sector companies listed on the Indonesian Stock Exchange (IDX) during the 2020-2024 period. Financial performance in this study is measured using the Return on Assets (ROA) ratio. Capital structure is represented by the Debt-to-Equity Ratio (DER), while intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC) method, and firm size is calculated based on the natural logarithm of total assets. This study employs a quantitative approach using panel data regression analysis. The sample consists of 27 banking companies listed on the IDX, resulting in a total of 135 observations. The sampling technique used was purposive sampling, and the data were processed using EViews software. The results indicate that capital structure, as measured by DER, has no significant effect on financial performance. On the other hand, intellectual capital and firm size are found to have a positive and significant effect on financial performance. These findings suggest that intellectual value and company scale play a critical role in enhancing banks' financial performance, where the amount of debt does not have a direct impact.